Manajemen Strategis PP. Avia Avian Tbk - Elvina Yohana Santoso (Syntax Literate, 2023)
Strategic management is a crucial approach for organizations in facing a dynamic changing business environment. PT. Avia Avian Tbk, as a company operating in an industry, faces diverse challenges and opportunities in a rapidly changing environment. This study aims to analyze the strategic management approach implemented by PT. Avia Avian Tbk in facing market and technology changes. This research uses qualitative analysis methods by conducting an in-depth review of the company's documented strategy and interviews with key stakeholders in the company. The results showed that PT. Avia Avian Tbk has adopted a strategic management approach that focuses on [e.g. product differentiation, operational efficiency, new market penetration, or technological innovation]. These strategic steps are geared towards maximizing value for the company's stakeholders, including shareholders, customers, employees, and society. One of the important aspects in the strategic management of PT. Avia Avian Tbk is the use of environmental analysis tools such as PESTEL (Political, Economic, Social, Technology, Environmental, Law) to identify external factors that may affect their business. In addition, the company has also set measurable long and short-term goals, and implemented performance measurement and monitoring mechanisms to ensure the achievement of these goals. Overall, this study provides insight into the strategic management approach applied by PT. Avia Avian Tbk and how the company strives to optimize its business performance in the midst of a changing business environment. The research also provides a foundation for other companies in similar industries to understand best practices in dealing with similar challenges.